Chave para adultos de dípteros (Muscidae, Fanniidae, Anthomyiidae) associados ao ambiente humano no Brasil - Claudio José Barros de Carvalho; Maurício Osvaldo Moura; Paulo Bretanha Ribeiro (Revista Brasileira de Entomologia, 2002)
Key to adult flies of dipterous species (Muscidae, Fanniidae, Anthomyiidae) associated to human habitats in Brazil. An identification key for the main 33 species of Muscidae, Anthomyiidae and Fanniidae occurring in association to human habitats in Brazil is presented. Most of the characters used for identification of the species are illustrated. Based on literature records, a list of the 65 anthropic species known to Brazil is also included.